A malignant astrocytoma with uncommon angiocentric features and dot-like EMA expression - Kuncman, Wojciech; Braun, Marcin; Kuncman, Łukasz; Kupnicki, Piotr; Piotrowski, Michał; Jesionek-Kupnicka, Dorota; Kordek, Radzisław (Contemporary Oncology/Współczesna Onkologia, 2018)
Angiocentric features are uncommon in high-grade World Health Organisation (WHO) brain tumours, whilst they are typical for WHO grade I tumours, e.g. angiocentric gliomas. We present an unusual glial tumour that occurred in a 59-year-old man. The tumour had equivocal radiologic and histopathologic features, especially a characteristic angiocentric pattern, low-to-moderate Ki67, and dot-like epithelial membrane antigen expression. The tumour did not show features characteristic for glioblastoma; however, it recurred as glioblastoma four months later. Based on this case, we show that high-grade WHO brain tumours may show an angiocentric pattern typical for low-grade WHO brain tumours, such as angiocentric gliomas.